Pendidikan Moral Pada Mahasiswa dan Implikasi Dokumen Gereja Dignitas Infinita - Hemma Gregorius Tinenti; Erni Kanida (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
This research began with the author's anxiety regarding the low level of instillation and understanding of moral values ​​among students. This low understanding is demonstrated by students' treatment which is contrary to general morals and Christian morals in particular. Good moral understanding will certainly lead humans to respect the dignity of others. Therefore, through this study, the author voices the message conveyed by Pope Francis in the Dignitas Infinita document. This research was conducted among active students in the Catholic Religious Education study program, Pontianak State Catholic Religious College for the 2024/2024 Academic Year. The population of this research was 917 students and the sample of this research was 123 students. The method used in the research is a qualitative method, while the technique used to explore data is using a questionnaire. The data analysis technique used in the research is descriptive data analysis, meaning that the author explains the research data by linking the theory discussed in this research. The presentation of numbers and graphs is followed by the author's explanation and analysis to explain the research results in numerical form. The results of the research prove that students' understanding is still very low in terms of moral understanding, both general morals and Christian morals. So the author also suggests that future researchers conduct broader research on moral education implemented in Catholic families.